PEMBINAAN KETERAMPILAN BERBICARA DAN MENULIS BAHASA JAWA KELAS 3 DI MADRASAH IBTIDAIYYAH (Adi Widya: Jurnal Pendidikan Dasar, 2023)
Language skills involve both parties in communicating must both have productive skills in language, both orally and in writing. the researcher took writing skills and speaking skills which are two language skills that cannot be separated from most people, especially from students at MI NU Roudlotush Sholichin Sunggingan Kudus class 3. If these students have these two skills, it will be very easy to communicate with people around him. Especially in instilling and preserving Javanese culture. In this study, researchers used qualitative field research using phenomenological research types. From the results of observations and interviews at MI NU Roudlotush Sholichin Sunggingan Kudus in writing skills students were able to develop these skills in the form of implementation and coaching in learning Javanese as well as student experiences given to educators. in speaking skills students are able to carry it out, that way students can develop their abilities in speaking skills more. Javanese language learning is directed at improving students' ability to communicate using Javanese properly and correctly which includes four aspects of skills namely listening, reading, writing and speaking skills. Language skills involve both parties in communicating must both have productive or expendential skills in language, both orally and in writing as seen in speaking and writing activities.